Effects of fixation and enzymatic digestion on the immunohistochemical demonstration of laminin and fibronectin in paraffin embedded tissue. Issue 6 (June 1984) - Kirkpatrick, P; d'Ardenne, A J
Abstract : The effects of different fixatives and enzymatic digestion procedures on the immunohistochemical demonstration of fibronectin and laminin in paraffin embedded tissues have been compared. None of the fixatives tested enabled staining of these proteins without enzymatic digestion. No intracytoplasmic laminin was found either in fixed or in fresh frozen tissue. Fixation in formol acetic acid was unsatisfactory for demonstration of fibronectin; prolonged fixation in formol sublimate was unsatisfactory for demonstration of laminin. Optimal results were achieved after fixation in routine 10% formol saline. Trypsin was completely ineffective for unmasking laminin antigens except after fixation in ethanol acetic acid; it was only partially effective for showing fibronectin antigens. The best results were obtained with protease digestion, but pepsin was an adequate, although slightly less reliable, alternative. These enzymes may be used at lower concentrations than usually recommended.